2016
DOI: 10.3390/molecules21121635
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of New 3,4-Dihydroisoquinolin Derivatives Containing Heterocycle as Potential Anticonvulsant Agents

Abstract: Two novel series of 3,4-dihydroisoquinolin with heterocycle derivatives (4a-t and 9a-e) were synthesized and evaluated for their anticonvulsant activity using maximal electroshock (MES) test and pentylenetetrazole (PTZ)-induced seizure test. All compounds were characterized by IR, 1 H-NMR, 13 C-NMR, and mass spectral data. Among them, 9-(exyloxy)-5,6-dihydro-[1,2,4]triazolo [3,4-a] isoquinolin-3(2H)-one (9a) showed significant anticonvulsant activity in MES tests with an ED 50 value of 63.31 mg/kg and it sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Among them, 153 ( Figure 25 ) showed significant anticonvulsant activity in MES tests with an ED 50 value of 63.31 mg/kg and it showed wide margins of safety with protective index (PI > 7.9). A docking study of compound 153 in the benzodiazepine (BZD)-binding site of aminobutyric acid A (GABAA) receptor confirmed possible binding of compound 153 with the BZD receptors 175 .…”
Section: Fused-triazolonesmentioning
confidence: 94%
“…Among them, 153 ( Figure 25 ) showed significant anticonvulsant activity in MES tests with an ED 50 value of 63.31 mg/kg and it showed wide margins of safety with protective index (PI > 7.9). A docking study of compound 153 in the benzodiazepine (BZD)-binding site of aminobutyric acid A (GABAA) receptor confirmed possible binding of compound 153 with the BZD receptors 175 .…”
Section: Fused-triazolonesmentioning
confidence: 94%
“…Pentylenetetrazole was dissolved in 0.9% saline to allow subcutaneous injections to mice at a dose of 85 mg/kg. The failure to observe even a threshold seizure (a single episode of clonic spasms of at least 5 s duration) is defined as protection [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gupta et al reported five derivatives and evaluated for their anthelmintic activity against P. posthuma . From the result, compound 19a showed the potent vermicidal activity, and it exhibited the maximum paralysis time and 37.33 min of death time at 20 mg/mL concentration [ 47 , 48 ]. …”
Section: Main Textmentioning
confidence: 99%